PHYSICAL DEVELOPMENT OF ATHLETES OF CYCLIC SPORTS SPECIALIZING IN ATHLETICS AND CROSS-COUNTRY SKIING - Fedulova, D.V.; Serova, N.B. (Theory and Practice of Physical Culture, 2022)
Objective of the study is a comparative assessment of the development of physical qualities and anthropometric indicators of athletes specializing in athletics and cross-country skiing. Methods and structure of the study. 35 athletes took part in the study process. The level of sportsmanship of the studied - youth and adult sports categories; the average period of studies is 3.1±0.46 years. Results and conclusions. Athletes training in middle-distance running have a lower percentage of fat and a higher percentage of the muscle component of the body relative to cross-country skiers, however, the differences do not have a statistical significance of the results. In the diagnosis of physical qualities, it was revealed that athletes-athletes are more physically developed than skiers. The greatest differences are reflected in the indicators of flexibility and strength. At the same time, in terms of the main quality of endurance for these specializations, cross-country skiers slightly, but surpass track and field athletes in terms of performance.